Understanding the structure-activity relationship for additives selection in Zn metal batteries - Cai, Da-Qian (2024)
Detrimental dendrite growth and parasitic side reactions greatly hinder the implementation of aqueous metal batteries. Despite many reports on exploring electrolyte additives to mitigate these issues, the structure–activity relationship of the additives in terms of their adsorption configurations and anti-dendrite/corrosion effects has been rarely investigated. In this research, we demonstrate that the optimal adsorption configuration (determined by the position of –N sites) greatly affect the interfacial regulation of both electrodes. Pyridazine (Pyd) in its optimal configuration exhibit the best hydrophobicity, effectively inhibiting water-related side reactions but sacrificing the Zn2+ reactivity at the mean time. In contrast, Pyrimidine (Pym) synchronously supply abundant zincophilic sites to accelerate Zn2+ desolvation and guide uniform Zn nucleation without hydrogen evolution. This work builds up the relationship between molecular configuration and interfacial electrochemistry of Zn metal batteries, highlighting the necessity of considering interfacial adsorption configuration. This may shed light on the additive design for not only Zn but also other alkaline metal anodes in aqueous energy storage systems.